2021
DOI: 10.1108/jaoc-01-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related discourses in corporate annual reports: an exploratory study on the Bangladeshi companies

Abstract: Purpose The purpose of this study is to explore the gender-related discourses in the annual reports of the listed companies in Bangladesh. Design/methodology/approach To fulfill this objective, a sociological discourse analysis (SDA) of the gender-related texts in the annual reports of Bangladeshi companies (listed in the Dhaka Stock Exchange) was conducted. Sandberg and Holmlund’s (2015) organizational impression management tactics (description, praise, admission, defense and writing styles) was applied as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 50 publications
(140 reference statements)
2
24
0
Order By: Relevance
“…This is not surprising as there is a concern expressed in prior studies (see, e.g. Hossain et al, 2021) on gender inequality in corporate world in the context of both developed and developing countries. The mean value of banks' size (denoted as "SIZE") is 7.96, which is equivalent to 3,533 employees in each bank.…”
Section: Empirical Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is not surprising as there is a concern expressed in prior studies (see, e.g. Hossain et al, 2021) on gender inequality in corporate world in the context of both developed and developing countries. The mean value of banks' size (denoted as "SIZE") is 7.96, which is equivalent to 3,533 employees in each bank.…”
Section: Empirical Results and Discussionmentioning
confidence: 80%
“…This is not surprising as there is a concern expressed in prior studies (see, e.g. Hossain et al. , 2021) on gender inequality in corporate world in the context of both developed and developing countries.…”
Section: Empirical Results and Discussionmentioning
confidence: 80%
“…On the other hand, some works underline that female leadership could be a limiting factor for the fulfillment of business objectives [66,67] and that the exercise of their functions could assume negative traits. Other researchers, such as [68], emphasize instead the positive perception related to female leadership, which is characterized by personal security, independence, altruism, the entrepreneurial woman capable of creating change, and the ability to transform work into a vocation.…”
Section: Discussionmentioning
confidence: 99%
“…Disclosures on websites and in sustainability reports showed that efforts are made to perceive females as stakeholders, but these efforts are limited. Hossain et al (2021) analysed the gender-based disclosures in the annual corporate reports of Bangladeshi companies and found that gender-based disclosures are limited and have focused on equal opportunities, business activities targeted at women and corporate contribution to women’s welfare. Most of these gender-related discourses are only rhetorical in nature (Hossain et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hossain et al (2021) analysed the gender-based disclosures in the annual corporate reports of Bangladeshi companies and found that gender-based disclosures are limited and have focused on equal opportunities, business activities targeted at women and corporate contribution to women’s welfare. Most of these gender-related discourses are only rhetorical in nature (Hossain et al , 2021). Even when gender-related corporate disclosures do not appear in the public domain, accounting professionals may deem it appropriate to include additional information in the reports (Haniffa and Hudaib, 2007; García-Sánchez et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%